2022
DOI: 10.1007/s43441-021-00357-x
|View full text |Cite
|
Sign up to set email alerts
|

Why are not There More Bayesian Clinical Trials? Perceived Barriers and Educational Preferences Among Medical Researchers Involved in Drug Development

Abstract: Objective and Background The clinical trials community has been hesitant to adopt Bayesian statistical methods, which are often more flexible and efficient with more naturally interpretable results than frequentist methods. We aimed to identify self-reported barriers to implementing Bayesian methods and preferences for becoming comfortable with them. Methods We developed a 22-question survey submitted to medical researchers (non-statisticians) from industry, academia, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…There would be even more additional training required if the alternative to P values was Bayesian analysis. A recent survey found that almost half of 323 clinical trial medical researchers reported insufficient knowledge as the main reason they did not use Bayesian statistics [ 73 ]. Thus, changing the P value threshold seems, at this point, a modest proposal that might help correct the problem of false positive results identified in many social and behavioral academic disciplines.…”
Section: Discussionmentioning
confidence: 99%
“…There would be even more additional training required if the alternative to P values was Bayesian analysis. A recent survey found that almost half of 323 clinical trial medical researchers reported insufficient knowledge as the main reason they did not use Bayesian statistics [ 73 ]. Thus, changing the P value threshold seems, at this point, a modest proposal that might help correct the problem of false positive results identified in many social and behavioral academic disciplines.…”
Section: Discussionmentioning
confidence: 99%
“… 28 A lack of familiarity with Bayesian concepts within the medical community must be overcome prior to more widespread adoption into clinical practice and incorporation into prospective studies. 29 Furthermore, many currently published Bayesian analyses represent unplanned, post hoc analyses of primary studies, often in an attempt to overcome underpowering. Although these reports add to the interpretation of their associated primary studies, a key take-away should be that more clinical trials should be analyzed primarily using Bayesian techniques as they may overcome many challenges clinical researchers face.…”
Section: Discussionmentioning
confidence: 99%
“…Similar barriers are present in the industry. The Drug Information Association Bayesian Scientific Working Group surveyed organizations and found that insufficient practical knowledge was a hurdle to adopting Bayesian approaches 42 . This issue is not unique to large or small companies.…”
Section: Barriers To Widespread Adoption Of Bayesian Analysesmentioning
confidence: 99%